The differential equation can be solved using an integrating factor. An integrating factor for this differential equation is e^(int(2)dx)=e^(2x).

Multiplying both sides of the differential equation by e^(2x) gives:
e^(2x)f'(x) - 2e^(2x)f(x) = e^(3x)

Now, we can use the product rule for derivatives, which states that:
(e^(2x)f(x))' = e^(2x)f'(x) + 2e^(2x)f(x)

Therefore, we can write:
(e^(2x)f(x))' = e^(3x)

Integrating both sides with respect to x gives:
e^(2x)f(x) = (1/3)e^(3x) + C

where C is a constant of integration.

Finally, we can solve for f(x) by dividing both sides by e^(2x):
f(x) = (1/3)e^x + Ce^(-2x)

where C is determined by initial or boundary conditions.


Q) solve the above differential equation with initial condition f(0)=1



The initial condition f(0) = 1 tells us that when x = 0, the function f(x) has a value of 1. We can use this information to find the constant of integration C.

Substituting x = 0 into the general solution, we get:
f(0) = (1/3)e^0 + Ce^(-2*0) = (1/3) + C = 1

So, C = (1 - 1/3) = 2/3

Therefore, the solution to the differential equation f'(x) - 2f(x) = e^x with the initial condition f(0) = 1 is:
f(x) = (1/3)e^x + (2/3)e^(-2x)

Posted by 살레시오

The determinant of a 3x3 matrix A, denoted as det(A) or |A|, is a scalar value that can be calculated from the elements of the matrix.

The formula for the determinant of a 3x3 matrix is:

| a b c |
| d e f | = a*(ei - fh) - b*(di - fg) + c*(dh - eg)
| g h i |

where a, b, c, d, e, f, g, h, i are the elements of the matrix A.

It can also be computed using the rule of Sarrus which is a mnemonic device to remember the formula for 3x3 determinant:

| a b c |
| d e f | = aei + bfg + cdh - afh - bdi - ceg
| g h i |

The determinant of a matrix has many uses in linear algebra and it is used to determine the invertibility of a matrix, it is also used to calculate the area or volume of a parallelepiped spanned by the columns or rows of the matrix.

Posted by 살레시오

To find the derivative of xsec^2(x) with respect to x, we can use the chain rule. First, we need to express xsec^2(x) in terms of its reciprocal function, csc(x).

xsec^2(x) = 1/(csc(x))^2

Using the reciprocal function identities, csc(x) = 1/sin(x) and sec(x) = 1/cos(x), we can then express xsec^2(x) as:

xsec^2(x) = (cos(x))^2/(sin(x))^2

Now we can take the derivative of xsec^2(x) using the chain rule:

d/dx(xsec^2(x)) = 2cos(x)(-sin(x))(cos(x))/(sin(x))^2 + (cos(x))^2(-1/sin(x))*(cos(x))

Simplifying the equation, we get:

d/dx(xsec^2(x)) = tan(x)*sec^2(x)

So the derivative of xsec^2(x) with respect to x is tan(x)*sec^2(x).

Posted by 살레시오